Six Sigma Analysis as an Approach to Improve Quality of Corrugated Zinc Sheet Product - Cahya, Handy Nur (Jurnal Penelitian Ekonomi dan Bisnis, 2021)
Every manufacturing company will strive to create the best quality products. This is also done by PT. CMSM, a steel company, is producing corrugated zinc products. In several production periods, the defective product values were still found that exceeded the tolerance limit value set at 0.5% in corrugated zinc products. These problems are, of course, very detrimental to the company, so it’s essential to control the quality of corrugated zinc products. This study aimed to determine the factors that cause product defects, propose plans to improve product quality, and provide managerial recommendations based on Six Sigma analysis. Data collection techniques are carried out through observation, interviews, and documentation. Based on the study results, it is known that DPO is 0.000885 and DPMO is 884.6028. At this time, the company is at the level of 4.64 sigma with CTQ (Critical to Quality) folded zinc sheet, cut size is not according to standard, thickness is not according to standard, uneven coating layer and perforated zinc sheet. Based on the analysis, five factors cause product defects: humans, machines, methods, materials, and the environment. To improve quality, the company should improve their quality control through 5W + 1H analysis, namely by providing training to employees, periodic machine maintenance and ensuring that the SOPs that have been made are implemented correctly and adequately. Keywords: six sigma, DMAIC, product defect, quality control, manufacturing